Pharmacogenetics of proton pump inhibitors - M. V. Leonova (Медицинский совет, 2015)
Proton pump inhibitors (PPI) are currently the most effective class of antisecretory drugs widely used in the treatment of non-ulcer dyspepsia, reflux esophagitis and GERD, peptic ulcer disease and H. pilory infection, as well as NSAID-associated gastric lesions. Despite the common mechanism of action and pharmacological effects of this class of drugs, there is clinical inter-individual variability of their effect on acid production determined by pharmacokinetic and pharmacogenetic factors. As a result, the clinical efficacy of treatment of acid-base disorders and eradication of H. pilory is decreased.